2022
DOI: 10.3346/jkms.2022.37.e40
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variations of 31 γ-Chromosomal Short Tandem Repeats Analyzed by Massively Parallel Sequencing in Three U.S. Population Groups and Korean Population

Abstract: Background Rapidly mutating (RM) Y-chromosomal short tandem repeats (Y-STRs) have been demonstrated to increase the possibility of distinguishing between male relatives due to a higher mutation rate than conventional Y-STRs. Massively parallel sequencing (MPS) can be useful for forensic DNA typing as it allows the detection of sequence variants of many forensic markers. Here, we present sequence variations of 31 Y-STRs including nine RM Y-STRs (DYF387S1, DYF399S1, DYF404S1, DYS449, DYS518, DYS570,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…An increase of at least 40% in the total number of alleles due to sequence allele variations detected by MPS compared to those identified by CE was also confirmed by other authors [26,46,48,49,[52][53][54], as well as the observation that the most varied allele sequences occurred in DYF387S1 and DYS389II markers [26,34,48,49,51,53]. Concerning the presence of N-1 stutter, the information recovered from other works that had evaluated them agreed with the findings of this study: for example, the highest value of the N-1 stutter ratio was observed at DYS481, which has a trinucleotide repeat [46,51].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…An increase of at least 40% in the total number of alleles due to sequence allele variations detected by MPS compared to those identified by CE was also confirmed by other authors [26,46,48,49,[52][53][54], as well as the observation that the most varied allele sequences occurred in DYF387S1 and DYS389II markers [26,34,48,49,51,53]. Concerning the presence of N-1 stutter, the information recovered from other works that had evaluated them agreed with the findings of this study: for example, the highest value of the N-1 stutter ratio was observed at DYS481, which has a trinucleotide repeat [46,51].…”
Section: Discussionsupporting
confidence: 79%
“…Specifically, poor or inconsistent results for the DYS392 locus, due to a low reads coverage, even when the total sample readings were high, were described and this was also reported by the manufacturer in the manual of the FSSP kit. [11,28,39,46,48,49] Concordance between CE and MPS above 99% in allele calling was confirmed on the basis of their size. The rare discrepancies that have been highlighted in other works at the DYS392, DYS393, DYS481, DYS439, and DY576 markers have been caused by the presence of SNPs in the flanking region, primers binding site mutations, and by the use of different primer sequences employed by CE and MPS systems [26,34,46,[48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…An interpretation threshold of 500 reads for homozygotes and 100 reads for heterozygotes was applied to autosomal loci according to Hölzl-Müller et al [51]. Additionally, an interpretation threshold of 100 reads was also applied to Y-STRs according to Moon et al [52]. Reads above 50× coverage but below the interpretation threshold were considered "Below-Threshold" (BT).…”
Section: Discussionmentioning
confidence: 99%
“…They have an independent branch of the Indo-European language family. The Armenian and the Kurds historically are living together in one empire or divided between the neighboring empires (Martirosyan, 2014). Numerous DNA-based data are utilized to examine the phylogeography, origins, and demographic history.…”
Section: Introductionmentioning
confidence: 99%